Pathophysiologic Mechanisms of Hypothermia-Induced Pancreatic Injury in a Rat Model of Body Surface Cooling. Issue 2 (February 2021) - Inoue, Hiroyuki; Harada, Keisuke; Narimatsu, Eichi; Uemura, Shuji; Aisaka, Wakiko; Bunya, Naofumi; Nomura, Kazuhito; Katayama, Yoichi
Abstract : Objective: The mechanisms underlying hypothermia-induced pancreatic injury are unclear. Thus, we investigated the pathophysiology of hypothermia-induced pancreatic injury. Methods: We created a normal circulatory model with body surface cooling in rats. We divided the rats into control (36°C–38°C), mild hypothermia (33°C–35°C), moderate hypothermia (30°C–32°C), and severe hypothermia (27°C–29°C) (n = 5 per group) groups. Then, we induced circulatory failure with a cooling model using high-dose inhalation anesthesia and divided the rats into control (36°C–38°C) and severe hypothermia (27°C–29°C) (n = 5 per group) groups. Serum samples were collected before the introduction of hypothermia. Serum and pancreatic tissue were collected after maintaining the target body temperature for 1 hour. Results: Hematoxylin and eosin staining of the pancreas revealed vacuoles and edema in the hypothermia group. Serum amylase ( P = 0.056), lactic acid ( P < 0.05), interleukin 1β ( P < 0.05), interleukin 6 ( P < 0.05), and tumor necrosis factor α ( P = 0.13) levels were suppressed by hypothermia. The circulatory failure model exhibited pancreatic injury. Conclusions: Hypothermia induced bilateral effects on the pancreas. Morphologically, hypothermia induced pancreatic injury based on characteristic pathology typified by vacuoles. Serologically, hypothermia induced protective effects on the pancreas by suppressing amylase and inflammatory cytokine levels.